Problematic video-streaming: a short review. (December 2022) - Rahat, Maryam; Mojgani, Juliette; Lethbridge, Grace; Al-Bya, Hashim; Patterson, Beth; Goldman Bergmann, Carolina; Van Ameringen, Michael
Abstract : Video-streaming typically describes watching live or prerecorded videos online. This behavior has significantly increased over the past two years in tandem with the global COVID-19 pandemic. The literature describing this behavior is still in its infancy, therefore, it is not well-characterized and our understanding is thereby limited. Different forms of problematic video-streaming have varying prevalence rates in the literature and each requires further operationalization. Overall, the various presentations of problematic video-streaming have been found to be associated with poor mental and physical health and linked to increased impulsivity, reduced academic and work performance, and lower quality of life. This article explores the current literature surrounding the definition, prevalence, validated assessments, associated factors, motivations, and available treatments for problematic video-streaming. Highlights: Video-streaming use, particularly live streaming, increased in the last two years. Problematic video-streaming has been inconsistently defined in the literature. Male sex and younger age are associated with problematic live-video-streaming. Other risk factors include loneliness, poor mental health, and low self-control. Adverse consequences include reduced life satisfaction and social impairments.